Shariah risk management process for Islamic financial institutions in the context of shariah governance framework 2010 - Hassan, Rusni; Othman, Ahmad Azam; Omar, Muhammad Naim; Mohd Napiah, Mohammad Deen; Abdullah, Mohamad Asmadi; Yussof, Adnan; Ab. Karim, Mohd. Syahmi (UUM Press, 2017)
Shariah compliance is the backbone of Islamic banks. As an institution established within the ambit of Shariah, Islamic banks are expected to ensure that their aims, activities, operations and management adhere to the Shariah principles and values. Failure to comply with Shariah, will expose Islamic Financial Institutions (IFIs) to Shariah non-compliance risk. Subsequently, it is an essential duty of the IFIs to manage Shariah risk properly. In order to effectively manage the risk vulnerability of the IFIs, proper measures for risk management have been put in place in different frameworks that are either domestic or international based. In the Malaysian context, IFIs are guided by relevant regulations such as the Shariah Governance Framework 2010, IFSB principles and Islamic Financial Services Act 2013 with regards to Shariah risk management. This research examined the regulatory requirements of the Shariah risk management process for Islamic financial institutions that operate in Malaysia, in the context of the Guidelines on Shariah Governance Framework 2010 issued by the Central Bank of Malaysia. The paper discusses the concept of “risk”, “Shariah risk” and “Shariah non-compliant risk” in the context of Islamic Financial Institutions and also examines the process adopted by the Malaysian IFIs in managing the Shariah risk. The hypotheses that the paper seeks to establish are that there are differences between the concept of Shariah risk and Shariah non-compliant risk; and that the Shariah risk management process adopted by the IFIs are different than the conventional risk management process due to the unique features and requirements of the IFIs.